ADAPTASI DAN INTERAKSI SOSIAL.BUDAYA ORANG LAUT DI DESA SUNGAI LAUT KECAMATAN TANAH MERAH INDRAGIRI HILIR - Sitti Rahmah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
This writting intent to know adaptation pattern and social interaction culturizes Oceanic Person at sylvan An River Regenry Raddled district Oceanic lndragiri Downstream. It is looked on absorbing because Oceanic Person is looked on asprimitive's society or present teminology to be called by devastated Custom Comunnity society. They have alone uniqueness in patern behavior and system is alone point. Evenless Oceanic Person on their p receding epoch have once lived and wandering allong river Indragiri and untrammeled Oceanic. Since Year 1996 they all where declared for was rising the whole lot at continent. And so do thing it and patterns social adaptation culturize. They do to adapt inparticular while happen social activity that at mobilize by silvan head mother